2019
DOI: 10.1210/en.2019-00450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GLP-1 Receptor Agonists in the Cardiometabolic Complications in a Rat Model of Postmenopausal PCOS

Abstract: Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenism and ovulatory dysfunction. Women with PCOS have an elevated prevalence of cardiometabolic risk factors that worsen after menopause. Liraglutide (Lira), a glucagon-like peptide-1 receptor agonist, has shown beneficial metabolic effects in small clinic trials in reproductive-age women with PCOS. We have shown that chronic hyperandrogenemia in an experimental model of postmenopausal PCOS is associated with an adverse cardiometabolic profile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
1
25
1
Order By: Relevance
“…Our PCOS model mimics several of the cardiometabolic features observed in women with PCOS, such as increases in BP and BMI, and decreases in insulin sensitivity. BP in this PCOS model is elevated by ~10 mmHg [ 25 , 29 , 30 ]. We also previously reported that blocking the RAS with an ACE inhibitor eliminated BP differences between treated PCOS and control rats [ 30 ], implicating activation of the RAS in the elevation of BP in our model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our PCOS model mimics several of the cardiometabolic features observed in women with PCOS, such as increases in BP and BMI, and decreases in insulin sensitivity. BP in this PCOS model is elevated by ~10 mmHg [ 25 , 29 , 30 ]. We also previously reported that blocking the RAS with an ACE inhibitor eliminated BP differences between treated PCOS and control rats [ 30 ], implicating activation of the RAS in the elevation of BP in our model.…”
Section: Discussionmentioning
confidence: 99%
“…BP in this PCOS model is elevated by ~10 mmHg [ 25 , 29 , 30 ]. We also previously reported that blocking the RAS with an ACE inhibitor eliminated BP differences between treated PCOS and control rats [ 30 ], implicating activation of the RAS in the elevation of BP in our model. Indeed, women with PCOS have hyperreninemia [ 23 ] and blockade of the AT1R was effective in decreasing the BP of women with PCOS [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations